Searching for the Sane Society: Eric Fromm’s Contributions to Social Theory - Brennen, Bonnie (Javnost-The Public, 2006)
More than fifty years after Erich Fromm’s The Sane Society was first published, it remains an important work, surprisingly contemporary in scope, with particular relevance to scholars working in social theory and media studies. Fromm’s primary emphasis is on evaluating the sanity of contemporary western societies, which he suggests often deny its citizens’ basic human needs of productive activity, self-actualisation, freedom, and love. He suggests that the mental health of a society cannot be assessed in an abstract manner but must focus on specific economic, social, and political factors at play in any given society and should consider whether these factors contribute to insanity or are conducive to mental stability. Ultimately The Sane Society provides a radical critique of democratic capitalism that goes below surface symptoms to get to the root causes of alienation and to suggest ways to transform contemporary societies to further the productive activities of its citizens. Fromm envisions the refashioning of democratic capitalist societies based on the tenants of communitarian socialism, which stresses the organisation of work and social relations between its citizens rather than on issues of ownership.